2019
DOI: 10.1002/admi.201900157
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Interfacial Elastic Contact in Stacking Perovskite Solar Cells

Abstract: architecture that can be fabricated based on this cell. Examples of such devices are planar heterojunctions and mesoscopic structures, which have already exhibited very impressive performance. However, the cost, stability, and large-scale production requirements to realize commercialization of these cells should be considered. [5][6][7] Hence, many new kinds of structures based on developed alternative materials and protocols have been designed to solve the problems of the traditional cell architectures (usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Hence, a~90% transparency in the visible light and high conductivity to electrons or holes are the anticipated characteristics for a contact/window electrode while good mechanical flexibility is also required for creating bendable surfaces. To facilitate an efficient charge collection, the work function of the electrode material has to be considered for choosing an appropriate contact for holes and electrons separately [191][192][193]. Once the TCEs are fixed, the other electrode can be any material with reasonably high conductivity to the opposite charge carriers even if the material has poor transmittance.…”
Section: Selection Criteria For Contact Electrodesmentioning
confidence: 99%
“…Hence, a~90% transparency in the visible light and high conductivity to electrons or holes are the anticipated characteristics for a contact/window electrode while good mechanical flexibility is also required for creating bendable surfaces. To facilitate an efficient charge collection, the work function of the electrode material has to be considered for choosing an appropriate contact for holes and electrons separately [191][192][193]. Once the TCEs are fixed, the other electrode can be any material with reasonably high conductivity to the opposite charge carriers even if the material has poor transmittance.…”
Section: Selection Criteria For Contact Electrodesmentioning
confidence: 99%
“…For PC perovsikte solar cells it was reported that good elastic contact and high conductivity are the two basic requisites to achieve good interfacial contact when stacking laminated parts, adding some further constraint on the choice of CTLs. [ 161 ] The authors showed that PEDOT:PSS had superior conductivity and elasticity, enabling for substantial improvement in FF and J SC in devices. This pivotal aspect of effective SCs integration quests for more research and development on the properties of the interfaces between SC films and CTLs, whereas valuable information on the role of the interfaces in PC pervoskite solar cells was extensively reviewed elsewhere, [ 161 ] and can certainly contributes to advances in SC devices.…”
Section: Mapx Bulk Crystals and Thin Films For Solar Cellsmentioning
confidence: 99%
“…[ 161 ] The authors showed that PEDOT:PSS had superior conductivity and elasticity, enabling for substantial improvement in FF and J SC in devices. This pivotal aspect of effective SCs integration quests for more research and development on the properties of the interfaces between SC films and CTLs, whereas valuable information on the role of the interfaces in PC pervoskite solar cells was extensively reviewed elsewhere, [ 161 ] and can certainly contributes to advances in SC devices.…”
Section: Mapx Bulk Crystals and Thin Films For Solar Cellsmentioning
confidence: 99%
“…Moreover, the lamination with wet organic CTLs has been presented in tandem and semitransparent flexible perovskite solar cells . In addition, the lamination of dry organic layers on top of each other and directly on the perovskite absorber has been introduced . Recently, Dunfield et al presented a first proofā€ofā€concept of the pressureā€assisted lamination of two perovskite layers on top of each other, which is a promising technique suitable for industrial largeā€scale rollā€toā€roll fabrications .…”
Section: Introductionmentioning
confidence: 99%